ASSESSING ELECTRICAL AND PHYSICOCHEMICAL PERFORMANCE OF CHEMICALLY MODIFIED PALM OIL AS AN ALTERNATIVE TRANSFORMER LIQUID - Sharifah Masniah, Wan Masra; Yanuar Zulardiansyah, Arief; Andrew Ragai, Henry Rigit; Siti Kudnie, Sahari; Md Rezaur, Rahman; Mohd Saufee, Muhammad; Hamzah, Eteruddin (Malaysian Palm Oil Board, 2023)
Numerous studies have been conducted on enhancing the dielectric properties of palm oil (PO) with the addition of nanoparticles (NPs). However, insufficient emphasis was given to its physicochemical properties, which are also critical for the function of an insulating liquid. The high viscosity of PO is one of the key factors which deteriorates the usage of natural ester in general, and PO in our case. This study was intended to investigate the performance of chemically modified PO by adopting a sequential transesterification process – NPs addition. The present work explored the transesterified PO blended with insulative (SiO2) and semiconductive (ZnO) NPs at various concentrations (0.1-0.6 g L–1). The modified oils’ dielectric strength and physicochemical properties (density, kinematic viscosity, and water content) were measured using standard testing methods. The results showed that the transesterification process effectively reduced the viscosity of PO, and adding ZnO NPs substantially impacted the PO in terms of AC breakdown voltage, with an optimum performance at 0.2 g L–1 concentration of 85% improvement. In contrast, while using SiO2, its breakdown voltage decreased irrespective of the concentration